THE USE OF RETELLING STORY TO IMPROVE STUDENTS’ ABILITY IN SPEAKING - Susilo, Ridho; Marbun, Rismaya; Husin, Sy. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was concerned to know the effectiveness of retelling story in improving students’ ability in speaking to the eighth grade students of SMP PGRI 4 Pontianak. The researcher found students have limitations in speaking English because students are not accustomed to speaking in English. One of the reason is the teachers do not provide enough opportunities for students to practice speaking. Retelling story is conveying events in words, images and sounds, often by improvisation. This technique can help teacher provide opportunities for students to practice. The method of this research was pre-experimental research. The researcher measured the improvement of students’ speaking ability by collecting the data through performance test. The result of the mean score of the students’ pre-test was 63.28. While the students’ mean score of post-test after the treatment was 73.20. In addition, based on the computation of t-test was higher than t-table (3.92>2.063). It showed that the alternative hypothesis was accepted and the null hypothesis was rejected. In other words, retelling story in improving students’ ability in speaking is effective. Keywords: Speaking Ability, retelling story, pre-experimental Abstrak: Penelitian ini bertujuan untuk mengetahui efektivitas teknik menceritakan ulang dalam meningkatkan kemampuan siswa dalam berbicara untuk siswa kelas delapan SMP PGRI 4 Pontianak. Peneliti menemukan siswa memiliki keterbatasan dalam berbahasa Inggris karena siswa tidak terbiasa berbicara dalam bahasa Inggris. Salah satu alasannya adalah guru tidak memberikan kesempatan yang cukup bagi siswa untuk berlatih berbicara. Menceritakan ulang adalah menyampaikan peristiwa dengan kata-kata, gambar dan suara yang seringkali dilakukan dengan improvisasi. Teknik ini dapat membantu guru memberikan kesempatan bagi siswa untuk berlatih. Metode dalam penelitian ini adalah penelitian pre-eksperimental. Peneliti mengukur peningkatan kemampuan berbicara siswa dengan mengumpulkan data melalui tes performa. Hasil skor rata-rata pre-test siswa adalah 63,28. Sementara nilai rata-rata siswa dari post-test setelah treatment adalah 73,20. Selain itu, berdasarkan perhitungan t-tes lebih tinggi dari t-tabel (3,92> 2,063). Hal ini menunjukkan bahwa hipotesis alternatif diterima dan hipotesis nol ditolak. Dengan kata lain, cerita menceritakan kembali dalam meningkatkan kemampuan siswa dalam berbicara efektif. Kata kunci: kemampuan berbicara, menceritakan ulang, pre-experimental